AIDS Treatment and Human Rights in Context - Jones, P. author. aut Link
XV, 201 p.
Keywords: The book poses and explores questions about the roles of antiretroviral treatment and human rights in the global AIDS epidemic. A novel approach is used, which places treatment and human rights in the context of global debates, national struggles, and, especially, a case study of the lived experiences within a local community in South Africa.